Reverse Transcriptase Loop-Mediated Isothermal Amplification Assays (RTLAMP) for the Detection of Alfalfa Mosaic Virus from Forage Crops - Dawit, Woubit; Mulatu, Fikerte; Eshete, Yesuf; Negawo, Alemayehu T.; Muchugi, Alice; Jones, Christopher S. (2023)
AMV is one of the most economically important plant viruses and has a very wide host range including forage crops. To make sure that only seeds of satisfactory phytosanitary status are distributed to recipients in geographically diverse areas, the ILRI genebank routinely monitors seed-borne diseases during seed multiplication and in the field genebank. Current detection techniques for AMV include a dot-blot assay and a two-step Reverse Transcription Polymerase Chain Reaction (RT-PCR), both of which are time consuming. In the present study we developed a one step Reverse Transcriptase Loop-Mediated Isothermal Amplification (RT-LAMP) method for the sensitive and rapid detection of AMV from forage crops. For the assay, six different AMV specific primers were used, and a series of reactions were performed to identify optimal conditions. Amplicons were easily visualized by means of an in-tube colour indicator (SYBR Green I dye) with no requirement to run gel electrophoresis. The sensitivity of the RT-LAMP assay was assessed by comparing the optimized AMV RT-LAMP assay with the conventional RT-PCR. In RT-LAMP, an amplicon was generated up to 100 ag/μl dilutions in contrast to the conventional RT-PCR, where no amplification at 1 fg/μl and onwards, indicating that the detection limit of the AMV RT-LAMP assay is much lower than for the conventional RT-PCR. Finally, the optimized RT-LAMP assay was further validated on 40 field samples of different forage species and other important forage viruses. The developed RT-LAMP assay was specific and detected AMV from different forages with no cross reaction with other plant viruses (SBMV and potyvirus) tested in the ILRI-genebank seed multiplication/regeneration fields. The optimized RT-LAMP assay is an effective tool for the detection of AMV for field samples in diagnostic laboratories, and for quarantine applications.